PERILAKU STALKING REMAJA ZAMAN NOW DALAM BINGKAI TEORI BEHAVIOR (Studi terhadap Mahasiswa UIN Imam Bonjol Padang) - Afnibar afnibar; Dyla Fajhriani N (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Stalking as one of the behaviors that cannot be resolved in adolescents, as an effect of social media meetings. Stalking is a negative impact that can cause teens to be subject to legal sanctions, because they can consider the privacy of others. Knowing the rise of this research interested in studying stalking adolescents today in the framework of behavior theory (a study of UIN Imam Bonjol Padang Students). The purpose of this research is to describe the study of stalking adolescents today in terms of behavioral theory. The research method used is a qualitative method. Through in-depth interviews with 10 (ten) students (adolescents) UIN Imam Bonjol Padang. The results of the study showed that many students who did stalking research. A minimum of 2 hours and a maximum of 4 hours to stalk others. People who like to talk about ex girlfriends or boysfirends and people who like. Speaking done by students also influences behavior, in their lives, because they can interfere, talk, and their daily activities.